Balanced development of piezoelectricity, Curie temperature, and temperature stability in potassium–sodium niobhrate lead-free ceramics. Issue 41 (6th October 2016) - Zheng, Ting; Wu, Wenjuan; Wu, Jiagang; Zhu, Jianguo; Xiao, Dingquan
Abstract : (K, Na)NbO3 -based ceramics is highly expected to attain a balance development between piezoelectricity, Curie temperature and temperature stability. Abstract : (K, Na)NbO3 (KNN)-based ceramics are highly expected to attain a large piezoelectricity ( d 33 ), high Curie temperature ( T C ) and improved temperature stability. In this study, we modified both d 33 and T C by the construction of phase boundaries using a different chemical composition. As shown in this manuscript, the relationships among the composition, phase boundary and electrical properties can be well established. By designing a series of material systems of 0.95K0.40 Na0.60 NbO3 –0.05Bi0.5 M0.5 HfO3 M: Li, (Li, Na), (Li, K), (Li, Ag), (Li, Na, K), (Li, Ag, Na), (Li, Ag, K), (Li, Ag, Na, K), Ag, (Ag, Na), (Ag, K), (Ag, Na, K), Na, K, (Na, K), the orthorhombic–tetragonal (O–T) phase boundary can be well established and the enhanced d 33 of 330–370 pC N −1 and a high T C of 308–320 °C can then be attained simultaneously in the ceramics without Li. In particular, there is also an improved temperature stability of d 33 in KNN–BAH ceramics, i.e., a high d 33 of 200 pC N −1 and d 33 * of 300 pm V −1 can be shown by the ceramics even if the measurement temperatures reach 150 °C. As a result, a balanced development of three parameters can be well realized in KNN–BMH ceramics and we believe that this material system will give a clear understanding about the comprehensive behaviors of KNN-based ceramics with a high T C .